The Neuroprotective Role of Protein Quality Control in Halting the Development of Alpha-Synuclein Pathology - Manecka, Destiny-Love; Vanderperre, Benoît; Fon, Edward A.; Durcan, Thomas M. (Frontiers in Molecular Neuroscience, 2017)
Synucleinopathies are a family of neurodegenerative disorders that comprises Parkinson’s disease, dementia with Lewy bodies, and multiple system atrophy. Each of these disorders is characterized by devastating motor, cognitive, and autonomic consequences. Current treatments for synucleinopathies are not curative and are limited to improvement of quality of life for affected individuals. Although the underlying causes of these diseases are unknown, a shared pathological hallmark is the presence of proteinaceous inclusions containing the α-synuclein (α-syn) protein in brain tissue. In the past few years, it has been proposed that these inclusions arise from the self-templated, prion-like spreading of misfolded and aggregated forms of α-syn throughout the brain, leading to neuronal dysfunction and death. In this review, we describe how impaired protein homeostasis is a prominent factor in the α-syn aggregation cascade, with alterations in Protein Quality Control (PQC) pathways observed in the brains of patients. We discuss how PQC modulates α-syn accumulation, misfolding and aggregation primarily through chaperoning activity, proteasomal degradation, and lysosome-mediated degradation. Finally, we provide an overview of experimental data indicating that targeting PQC pathways is a promising avenue to explore in the design of novel neuroprotective approaches that could impede the spreading of α-syn pathology and thus provide a curative treatment for synucleinopathies.